In vitro micro-propagation of osbeckia reticulata bedd.(melastomataceae) an endemic medicinal plant of southern western ghats (Funded Work) - BOSCO LAWARENCE; MURUGAN K (International Journal of Pharma and Bio Sciences, 2018)
Osbeckia reticulata Bedd. (Melastomataceae) is an endemic medicinal plant of Southern Western Ghats and restricted along the high altitude regions of the grass lands. From the time immemorial, the tribal people have been using the coloured floral extract of the plant for curing many ailments. Chemically the compounds are anthocyanins. It is necessary to design an in vitro method for mass propagation, sustainable utilization and its conservation. A simple micro propagation method for mass multiplication of O. reticulata is being attempted in this study. Explants harvested from natural habitat were used to establish in vitro cultures. The nodal shoot and leaf segments were surface-sterilized and cultured on Murashige and Skoog (MS) medium along with growth additives. Cytokinins such as thidiazuron (TDZ), benzyl adenine (BA), and kinetin (KIN) were used in various combinations with auxins like indole butyric acid (IBA) and indole acetic acid (IAA). An average of 22.25 shoots was produced from the medium fortified with 0.85 mg/l TDZ, as compared to 3.5 mg/l BA yielded only 18.75 shoots. More than 50 shoots were produced in 1.35 mg/l TDZ from green compact callus through indirect organogenesis. 90% of the in vitro-produced shoots were well rooted with 1 mg/l of IAA. The plantlets were transferred to pots containing sterile medium with a mixture of peat soil: perlite: vermiculite (1:1:1 v/v) in the greenhouse. 95% of the plantlets were hardened in the pots within 15 days. The hardened plants were then transferred to black polybags in the nursery. Field transferred plants were growing normally with profuse flowering. The protocol developed was reproducible. From a single nodal segment approximately 1500 hardened plants could be regenerated within a span of 180 days.